Kurangnya Minat Baca Anak Generasi Alpha Di Era Perkembangan Teknologi - Muhamad Haykal Muttaqin; Adam Andreansyah; Reza Mauldy Raharja (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The alpha generation is the children that the millenial generation has left behind. This article was written by Mark Mc Crindle and published in the Business Insider magazine (Christina Sterbenz, 2015). The Alpha Generation (2011–2025) is the most advanced generation in terms of digital technology and the least advanced generation in comparison to the previous generation. Every day, almost 2.5 million children of the Alpha Generation are born into the world. The generation most familiar with the internet over the long term is Gen A. Mc Crindler also asserts that the Alpha generation is not averse to technology, somewhat socially adept, somewhat creative, and somewhat independent. Alpha generators require quick and somewhat chaotic processes. By enticing them with a technology, they become socially alienated. This article aims to understand the challenges faced by the Alpha Generation in the Industrial Revolution. For many people, literacy is a familiar language. Literasi is a concept with a complex, dynamic, and ever-changing definition that is defined by several methods with extreme caution. According Keywords: Literacy, Technology, Development, and Generation Alpha. to an online Merriam-Webster dictionary, the words